Concise synthesis of the bioactive natural polyhydroxynaphthoate parvinaphthol B via Hauser-Kraus annulation. Issue 51 (20th December 2017) - Ahn, Sungwan; Han, Young Taek
Graphical abstract: Highlights: The first synthesis of the parvinaphthol B was presented. The efficient synthetic route toward polyhydroxynaphthoate skeleton was described. The selective ether-bond cleavage was also investigated. Abstract: Herein, we describe the first total synthesis of parvinaphthol B, a polyhydroxynaphthoate derived from the root of Pentas parvifolia which exhibits cytotoxic effects against the TNBC cell line. The key feature of the synthesis involves a Hauser-Kraus annulation to provide the polyhydroxynaphthoate skeleton. The synthesis requires only six linear steps and afforded the product in 26.5% overall yield, thus representing a simple method for the further preparation of analogs and biological studies.